Farming as food as medicine in Tanzania: reviving traditional knowledge for health, nutrition, and sustainability - Leonard R. Ndibalema; Joseph Kalonga (Frontiers in Nutrition, 2026)
Tanzania faces a complex nutrition and public health challenge characterized by persistent undernutrition, micronutrient deficiencies, and an increasing burden of diet-related non-communicable diseases. At the same time, traditional farming systems that historically supplied diverse, nutrient-dense foods are being weakened by urbanization, climate variability, market pressures, and dietary transitions. This narrative review examines farming as food as medicine in Tanzania by synthesizing literature on indigenous crops, agroecology, agrobiodiversity, dietary diversity, public health nutrition, and sustainable food systems. The review highlights how traditional crops such as lablab, cowpea, sorghum, millet, cassava leaves, and indigenous vegetables contribute to dietary quality, preventive health, climate resilience, and cultural continuity. It further discusses the roles of social determinants, gender, public health professionals, nutrition-sensitive agriculture, and policy integration in strengthening food-based health strategies. The review argues that smallholder farming systems should be understood not only as sources of food and income, but also as preventive public health infrastructure. Revitalizing traditional food systems and agroecological farming can contribute to improved nutrition, reduced disease risk, environmental sustainability, and more resilient livelihoods in Tanzania.